O processo de criação de conhecimento organizacional durante a elaboração dos relatórios de sustentabilidade: um estudo de caso em uma organização de grande porte do setor de produtos de beleza - Mello, Josiane (2012)
This study aims to identify the phases of organizational knowledge creation during the preparation of sustainability reports of a large company in the business of beauty products having as background the theory of organizational knowledge creation Nonaka and Takeuchi (1997, 2008). To this end, we sought initially to know the sources of information internal and external (formal and informal) used for the acquisition of knowledge by staff that operates the reporting organization's sustainability study. We also sought to understand how is the process of creating organizational knowledge during the preparation of sustainability reports, as well as the conversion of tacit and explicit knowledge for achieving global goals of the organization and sustainable. furthermore, we studied the conditions and factors that affect the process of knowledge creation based on the theory of Von Krogh, Ichijo and Nonaka (2001) to complement the theory proposed by Nonaka and Takeuchi (1997, 2008). This research is classified as applied, exploratory and descriptive approach with quantitative and qualitative analysis, in which we made use of the following: bibliographic, documentary and case study. The data collection instruments used were: questionnaire, semi-structured interview, the organization's sustainability reports from previous years (2009 and 2010) and other institutional documents available on the internet. The results of this study showed that the process of knowledge creation depends on data, information and knowledge from internal and external environment of the organization, where knowledge, resulting in a constant process of interaction, to be expanded organizationally, needs to be shared and distributed among team members who work in the preparation of sustainability reports of the studied company. Sources of information, when properly selected and operated, are great means of acquiring knowledge, making a quality differential to make sustainability reporting of an organization. the conversion of tacit and explicit knowledge helps the company studied in achieving global goals and sustainable through: heterogeneous composition of the team working on the preparation of sustainability reports, professional performance of this team runs through the three organizational levels: strategic, intermediate and operational, organizational culture focused on sustainability and use of it as an important means of storing and providing knowledge. Contexts compounds suitable for various conditions and factors can facilitate this process by promoting the flow of information and knowledge throughout the preparation of sustainability reports. The tools of information technology and communication, when used effectively, contributing in communication, collaboration and interaction among employees in that enable the exchange of information, ideas and experiences, thus leveraging the process of knowledge creation.